PENGARUH METODE MASERASI DAN SOXHLETASI TERHADAP KADAR FLAVONOID EKSTRAK ETANOL DAUN KEMANGI (Ocimum basilicum L) - Agung Budi Prasetyo; Angga Rahabistara Sumadji; Maria Fatmadewi Imawati (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2022)
Basil leaf (Ocimum basilicum L) is one of the plants which can be used as medicine, it can be used as an anti-microbial and an anti-free radical. Flavonoids were one of the chemical compounds in basil leaves (Ocimum basilicum L). This study aimed to compare the flavonoid total content level based on extraction method variance. The extraction methods were maceration and soxhletation. Flavonoid level was measured with Spectrophotometer UV-Vis and quercetin standard. Data results were analyzed with Mann-Whitney statistical test. The results showed that the flavonoid total content level from soxhletation was 9,3106% and from maceration was 6,2756%. The statistical test result showed that the significant value <0,05 which means there was a significant difference between the flavonoid total content level from maceration and soxhletation methods.